2016
DOI: 10.11144/javeriana.upsy14-4.erdr
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la restrictividad de dispositivos residenciales para personas con un diagnóstico psiquiátrico en el modelo de Salud Mental Comunitaria en Chile

Abstract: Los hogares y residencias protegidas son elementos centrales de la red asistencial que atiende a personas con un diagnóstico de trastorno mental severo, dentro del modelo de salud mental comunitaria. Este modelo tiene como uno de sus propósitos centrales estimular la autonomía y participación social de los usuarios. Se evaluó la restrictividad presente en estos dispositivos y factores asociados a su predicción. Se evaluaron 21 servicios residenciales mediante la escala de prácticas restrictivas que se aplicó a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although the number of beds in psychiatric hospitals has decreased, especially at the cost of fewer hospital beds for long-term care, there are indicators of human rights violations based on involuntary admission procedures, mechanical containment measures, confinement in isolation wards, overmedication, maltreatment, punishment, physical and sexual abuse. Also described is the lack of information regarding the number of people admitted and the reasons why they remain in a situation of abandonment and exclusion, as well as the absence of mechanisms to safeguard rights in these facilities (INDH, 2017).…”
Section: Mental Health System and Community Model In Chilementioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of beds in psychiatric hospitals has decreased, especially at the cost of fewer hospital beds for long-term care, there are indicators of human rights violations based on involuntary admission procedures, mechanical containment measures, confinement in isolation wards, overmedication, maltreatment, punishment, physical and sexual abuse. Also described is the lack of information regarding the number of people admitted and the reasons why they remain in a situation of abandonment and exclusion, as well as the absence of mechanisms to safeguard rights in these facilities (INDH, 2017).…”
Section: Mental Health System and Community Model In Chilementioning
confidence: 99%
“…Thirdly, with regard to respect for the rights of users of outpatient psychiatric services, the right to an independent life and to be included in the community are described as having a low level of compliance at the national level (Minoletti et al, 2015). It is also noted that residential support devices (homes and residential facilities) have restrictive rules that limit the ability of residents to make decisions in basic areas of their lives (Grandón Fernández et al, 2015). In this regard, it has been suggested that protected homes and houses, although they have played a central role in the implementation of the community model, reproduce asylum practices because they are highly regulated places with continuous staff supervision.…”
Section: Mental Health System and Community Model In Chilementioning
confidence: 99%